A work system analysis of the medication administration process in a Norwegian nursing home ward. (July 2020) - Odberg, Kristian Ringsby; Hansen, Britt Sætre; Aase, Karina; Wangensteen, Sigrid
Abstract: Nursing home patients often have multiple diagnoses and a high prevalence of polypharmacy and are at risk of experiencing adverse drug events. The study aims to explore the dynamic interactions of stakeholders and work system elements in the medication administration process in a nursing home ward. Data were collected using observations and interviews. A deductive content analysis led to a SEIPS-based process map and an accompanying work system analysis. The study increases knowledge of the complexity of the medication administration process by portraying the dynamic interactions between the major stakeholders in the work system, and the temporal flow of the activities involved. Secondly, it identifies facilitators and barriers in the work system linked to the medication administration process. Most barriers and facilitators are associated with the work system elements – tools & technology, organisation and tasks – and occur early in the medication administration process. Highlights: Nurses are the only professional stakeholders involved in all the stages of the MAP. Most barriers are associated with ordering, the first stage of the MAP. A novel description of the MAP by using SEIPS as a conceptual model is introduced.